ANALISIS FAKTOR YANG MEMPENGARUHI BEHAVIORAL INTENTION DAN USER BEHAVIOR PADA FINTECH SHOPEEPAY MENGGUNAKAN MODEL UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY (UTAUT) - Linda Lorenza Hafifah; Nengah Widya Utami; I Gst.Agung Prmaesti Dwi Putri (Jurnal Akuntansi Bisnis, 2022)
ABSTRACT: This study aims to determine the factors that can influence the interest of the Denpasar City Community in using ShopeePay fintech with the Unified Theory Of Acceptance And Use Of Technology (UTAUT) model. The data used in this study is primary data, where data is obtained directly from parties related to distributing questionnaires using google form. This study uses 2 sampling techniques, namely purposive sampling and convenience sampling. Validity and reliability testing of the instrument was carried out with SPSS software which was used to ensure that the questionnaire was valid and reliable. The data that has been obtained were analyzed using the Partial Least Square (PLS) method using smartPLS software. The results of the tests carried out indicate that the performance expectancy and effort expectation variables on the behavioral intention variable, the facilitating condition variable and the behavioral intention on the user behavior variable. Then the rejected hypothesis is the social influence variable on the behavioral intention variable.Keywords: Fintech ShopeePay, Unified Theory Of Acceptance And Use Of Technology (UTAUT), behavioral intentions, user behavior, smartPLS. ABSTRAK: Penelitian ini bertujuan untuk mengetahui faktor faktor yang dapat mempengaruhi minat Masyarakat Kota Denpasar dalam penggunaan fintech ShopeePay dengan model Unified Theory Of Acceptance And Use Of Technology (UTAUT).  Data yang digunakan dalam penelitian ini adalah data primer, dimana data diperoleh secara langsung dari pihak yang berkaitan dengan menyebarkan kuesioner menggunakan google form. Penelitian ini menggunakan 2 teknik sampling, yaitu Teknik purposive sampling dan convenience sampling Uji validitas dan uji reliabilitas instrumen dilakukan dengan software SPSS  yang digunakan untuk memastikan  kuesioner telah valid dan reliabel. Data yang telah didapatkan dianalisis dengan metode Partial Least Square (PLS) menggunakan software smartPLS. Hasil pengujian yang dilakukan mengindikasikan bahwa variabel performance expectancy dan effort expectation  terhadap variabel behavioral intention, variabel  facilitating condition dan behavioral intention terhadap user behavior. Kemudian hipotesis yang ditolak yaitu variabel social influence  terhadap variabel behavioral intention.Kata kunci: Fintech ShopeePay, Unified Theory Of Acceptance And Use Of Technology (UTAUT), behavioral intention, user behavior,  smartPLS.